The feasibility of wireless capsule endoscopy in detecting small intestinal pathology in children under the age of 8 years: a multicentre European study. Issue 11 (21st July 2009) - Fritscher-Ravens, A; Scherbakov, P; Bufler, P; Torroni, F; Ruuska, T; Nuutinen, H; Thomson, M; Tabbers, M; Milla, P
Abstract : Objective: To systematically evaluate the feasibility and methodology to carry out wireless capsule endoscopy (WCE) in children <8 years to define small intestinal pathology. Design: Prospective European multicentre study with negative prior investigation. Patients and interventions: 83 children aged 1.5–7.9 years were recruited. Initially, all were offered "swallowing" (Group 1) for capsule introduction. If this failed endoscopic placement (Group 2) was used and the Roth net, Advance or custom-made introducers were compared. Outcome measures: Primary endpoint: to determine pathology; secondary endpoint: comparison of capsule introduction methods. Results: Capsule introduction: 20 (24%) children aged 4.0–7.9 years (mean, 6.9 years; 14 male) comprising Group 1 were older (p<0.025) than 63 (76%) aged 1.5–7.9 years (mean, 5.25 years; 30 male) forming Group 2. Complications: Roth net mucosal trauma in 50%; no others occurred. The available recording apparatus was inappropriate for those <3 years. Indications: gastrointestinal bleeding: n = 30 (16 positive findings: four ulcerative jejunitis, four polyps, two angiodysplasia, two blue rubber blebs, two Meckel's diverticula, one anastomotic ulcer, one reduplication); suspected Crohn's disease: n = 20 (11 had Crohn's disease); abdominal pain: n = 12 (six positive findings: three Crohn's disease, two lymphonodular hyperplasia, one blue rubber bleb); protein loss: n = 9 (four lymphangectasia); malabsorption: n = 12 (seven positive findings: six enteropathy, one ascaris). No abnormalities overall: 45%. Conclusion: WCE is feasible and safe down to the age of 1.5 years. 20 children >4 years swallowed the capsule. The Advance introducer proved superior for endoscopic placement. The pathologies encountered showed age specificity and, unlike in adolescents, obscure gastrointestinal bleeding was the commonest indication.